Watchman Device Dislodgement Creating a Left Ventricular Outflow Tract Obstruction Requiring Emergency Cardiopulmonary Bypass. (23rd February 2022) - Roberts, Alex; Mach, Steven; Goebel, Jason; Palomino, Heather; Horstemeyer, Derek
Abstract : Left atrial appendage (LAA) occlusion device implantation is becoming a more common alternative for stroke prophylaxis in patients with nonvalvular atrial fibrillation (AF) who are not able to tolerate long-term anticoagulation. Studies suggest the procedure has a 98.5% successful deployment rate (Boersma et al., 2016). We present a case where a rare but known complication involving dislodgement and migration of an implanted Watchman LAA occlusion device led to functional stenosis of the aortic valve creating a left ventricular outflow tract (LVOT) obstruction necessitating emergency cardiopulmonary bypass in the electrophysiology lab to safely retrieve the device.